Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.

Temporal and spatial variation in C, N, S and trace element contents in the leaves of Quercus ilex within the urban area of Naples. (Environmental pollution (Barking, Essex : 1987), 2000)
This paper presents a comparative analysis of the concentrations of C, N and S and several trace elements (Fe, Mn, Na, Zn, Cu, V, Pb, Ni, Cr, Cd) in leaves of Quercus ilex, an evergreen oak, collected in the urban area of Naples in 1989 and 1996. The samplings were carried out from 25 urban sites (roads with different traffic flows as well as urban and suburban parks) and from two remote areas as controls. Relative to 1989, the values measured in 1996 denote a strong decrement of S, Fe, Na, Pb, and Cr, with the exception of S in control sites. By contrast, C, N and Cd contents were higher in 1996 than in 1989. Cu and Ni showed a conspicuous increment in control sites as well as in urban sites facing the sea and in the parks, while in all the other urban sites these elements decreased remarkably. No significant difference was found in the leaf contents of Mn, Zn and V measured in 1989 relative to 1996. Both in 1989 and 1996 the contents of N, S, Fe, Na, Cu, Pb, V, Ni, Cr and Cd were significantly higher in leaves from urban sites than in the controls, reflecting the high degree of contamination of the urban area. Concentration factors expressed as the ratio of road/control values for most of the elements were still very high in leaves collected in 1996, though remarkably lower than in 1989.

Temporal and spatial variation in C, N, S and trace element contents in the leaves of Quercus ilex within the urban area of Naples. - Alfani, a; Baldantoni, D.; Maisto, G.; Bartoli, G.; Virzo De Santo, A. (Environmental pollution (Barking, Essex : 1987), 2000)
This paper presents a comparative analysis of the concentrations of C, N and S and several trace elements (Fe, Mn, Na, Zn, Cu, V, Pb, Ni, Cr, Cd) in leaves of Quercus ilex, an evergreen oak, collected in the urban area of Naples in 1989 and 1996. The samplings were carried out from 25 urban sites (roads with different traffic flows as well as urban and suburban parks) and from two remote areas as controls. Relative to 1989, the values measured in 1996 denote a strong decrement of S, Fe, Na, Pb, and Cr, with the exception of S in control sites. By contrast, C, N and Cd contents were higher in 1996 than in 1989. Cu and Ni showed a conspicuous increment in control sites as well as in urban sites facing the sea and in the parks, while in all the other urban sites these elements decreased remarkably. No significant difference was found in the leaf contents of Mn, Zn and V measured in 1989 relative to 1996. Both in 1989 and 1996 the contents of N, S, Fe, Na, Cu, Pb, V, Ni, Cr and Cd were significantly higher in leaves from urban sites than in the controls, reflecting the high degree of contamination of the urban area. Concentration factors expressed as the ratio of road/control values for most of the elements were still very high in leaves collected in 1996, though remarkably lower than in 1989.
The following values have no corresponding Zotero field: accession-num: 15092919
Keywords: air pollution biomonitoring; leaf elemental analysis; no x; so 2; Trace Elements

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution